The impact of social, national and community-based health insurance on health care utilization for mental, neurological and substance-use disorders in low- and middle-income countries: A systematic review - Sumaiyah Docrat; Donela Besada; Susan Cleary; Crick Lund (Health Economics Review, 2020)
Background: Whilst several systematic reviews conducted in Low- and Middle-Income Countries (LMICs) have revealed that coverage under social (SHI), national (NHI) and community-based (CBHI) health insurance has led to increased utilization of health care services, it remains unknown whether, and what aspects of, these shifts in financing result in improvements to mental health care utilization. The main aim of this review was to examine the impact of SHI, NHI and CBHI enrollment on mental health care utilization in LMICs. Methods: Systematic searches were performed in nine databases of peer-reviewed journal articles: Pubmed, Scopus, SciELO via Web of Science, Africa Wide, CINAHL, PsychInfo, Academic Search Premier, Health Source Nursing Academic and EconLit for studies published before October 2018. The quality of the studies was assessed using the Effective Public Health Practice Project quality assessment tool for quantitative studies. The systematic review was reported according to the PRISMA guidelines (PROSPERO;2018; CRD42018111576).Results: Eighteen studies were included in the review. Despite some heterogeneity across countries, the results demonstrated that enrollment in SHI, CBHI and NHI schemes increased utilization of mental health care. This was consistent for the length of inpatient admissions, number of hospitalizations, outpatient use of rehabilitation services, having ever received treatment for diagnosed schizophrenia and depression, compliance with drug therapies and the prescriptions of more favorable medications and therapies, when compared to the uninsured. The majority of included studies did not describe the insurance schemes and their organizational details at length, with limited discussion of the links between these features and the outcomes. Given the complexity of mental health service utilization in these diverse contexts, it was difficult to draw overall judgements on whether the impact of insurance enrollment was positive or negative for mental health care outcomes. Conclusions: Studies that explore the impact of SHI, NHI and CBHI enrollment on mental health care utilization are limited both in number and scope. Despite the fact that many LMICs have been hailed for financing reforms towards universal health coverage, evidence on the positive impact of the reforms on mental health care utilization is only available for a small sub-set of these countries.
Keywords: 330; Social health insurance; National health insurance; Community-based health insurance; Mental health care; Developing countries; Health financing; Mental health; Health care utilization; Mental health care utilization; Mandatory health insurance